2020
DOI: 10.1002/sstr.202000081
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Ceria‐Based Materials in the Oxidation of Carbon Monoxide

Abstract: Carbon monoxide (CO) is a toxic and harmful gas pollutant. The realization of low‐temperature CO oxidation has been the focus of research. Also, CO oxidation as a typical model reaction is conducive to the in‐depth study of the catalytic reaction mechanism. Due to its unique oxygen storage/release capacity (OSC) and the easy transition between Ce3+ and Ce4+, CeO2 is widely used as a catalyst and catalyst support in many important reactions, especially the low‐temperature CO oxidation reaction. Herein, the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 189 publications
(238 reference statements)
0
22
0
Order By: Relevance
“…It was previously reported that the doping of rareearth metals into CeO 2 causes changes in the specific surface area, particle size, and morphology of ceria. 15 To ensure that the two samples had similar Pt surface loadings after deposition (the higher the surface loading, the easier it is for the Pt atoms to aggregate 16 ), different weight loadings were used to adjust for the difference in the surface area between the two samples (Figure 2a,b and Table 1). Neither Figure 2a,b nor the additional examples provided in Figure S1 (Supporting Information) provide any sign of aggregated or clustered Pt atoms on the surface of either support.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that the doping of rareearth metals into CeO 2 causes changes in the specific surface area, particle size, and morphology of ceria. 15 To ensure that the two samples had similar Pt surface loadings after deposition (the higher the surface loading, the easier it is for the Pt atoms to aggregate 16 ), different weight loadings were used to adjust for the difference in the surface area between the two samples (Figure 2a,b and Table 1). Neither Figure 2a,b nor the additional examples provided in Figure S1 (Supporting Information) provide any sign of aggregated or clustered Pt atoms on the surface of either support.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lattice fringes attest to the crystalline nature of the CeO 2 and Gd–CeO 2 supports in Figure a,b, respectively. It was previously reported that the doping of rare-earth metals into CeO 2 causes changes in the specific surface area, particle size, and morphology of ceria . To ensure that the two samples had similar Pt surface loadings after deposition (the higher the surface loading, the easier it is for the Pt atoms to aggregate), different weight loadings were used to adjust for the difference in the surface area between the two samples (Figure a,b and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen vacancies play important roles in oxides including catalysis [109][110][111][112], gas sensor applications [113], energy storage [114,115], electronic states [116] and in oxide interface systems [117][118][119][120][121] such as LaAlO3/SrTiO3 interfaces [122,123]. In the superconducting Nd0.8Sr0.2NiO2/SrTiO3 superconducting system, oxygen vacancies may be generated during the soft chemical reduction, which could contribute conducting channels and thus affect superconducting transitions.…”
Section: How About Oxygen Vacancies In Srtio3 Substrates After Chemic...mentioning
confidence: 99%
“…Air pollution represents an enormous threat to our health, raising widespread fears and concerns. [1][2][3] As one of the leading sources, automobile exhaust emission must be rigorously controlled, which requires high-performance catalysts to Inspired by the achievements and considering the diversity of emission pollutants, a dual-site strategy should be a potential route to upgrade the existed TWCs, however, the related synthetic approaches and investigation on structure-performance relationship are still rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution represents an enormous threat to our health, raising widespread fears and concerns. [ 1–3 ] As one of the leading sources, automobile exhaust emission must be rigorously controlled, which requires high‐performance catalysts to convert toxic CO, hydrocarbon and NO x to nontoxic CO 2 , H 2 O, and N 2 (three‐way catalysts, denoted as TWCs). [ 4–6 ] Despite great achievements made, the current TWCs still suffer from the relatively high ignition temperature and poor hydrothermal stability that cannot match the increasingly powerful engines, as well as the stricter and stricter emission regulations.…”
Section: Introductionmentioning
confidence: 99%